Principal Leadership and Teacher Self-Efficacy as Key Determinants of Teaching Performance in Inclusive Kindergarten Settings - Kurniasih, Kurniasih; Suparno, Suparno (Papanda Publisher, 2025)
Teacher effectiveness in inclusive kindergarten settings requires understanding multiple factors that influence performance. Limited research examines the combined effects of leadership, psychological, and pedagogical factors on inclusive early childhood education quality. This study investigated the influence of principal leadership, teacher self-efficacy, and instructional innovation on teaching performance among inclusive kindergarten teachers in East Kutai Regency, Indonesia. A quantitative causal associative design was employed with 90 inclusive kindergarten teachers selected through stratified random sampling across 18 sub-districts. Data were collected using validated questionnaires measuring principal leadership (α = 0.889), teacher self-efficacy (α = 0.853), instructional innovation (α = 0.935), and teaching performance (α = 0.824). Multiple linear regression analysis was conducted after confirming classical assumptions. Principal leadership (β = 0.610, p < 0.001) and teacher self-efficacy (β = 0.361, p < 0.001) significantly predicted teaching performance, while instructional innovation showed no significant influence (β = 0.043, p = 0.456). The model explained 78.3% of performance variance (Adjusted R² = 0.783, F = 107.869, p < 0.001). Principal leadership emerges as the strongest predictor of teaching performance in inclusive kindergarten settings, followed by teacher self-efficacy. The non-significant innovation effect suggests implementation challenges requiring further investigation. These findings support prioritizing transformational leadership development and self-efficacy enhancement programs for inclusive education improvement.